DISTANCE LEARNING EXPERIENCE IN GEORGIA UNIVERSITIES - Eliava, Lia (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The covid-19 pandemic has put the higher education system of Georgia in front of serious challenges. Universities have had to quickly adapt to distance learning methods. Two years of distance learning experience has shown that this method of learning has its advantages and disadvantages. The description of these parties in the paper is based on the personal experience of the author’s academic activity.